2014
DOI: 10.1186/1756-0500-7-712
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin status and predictors of anaemia among pregnant women in Mpigi, Uganda

Abstract: BackgroundAnaemia in pregnancy is a major public health problem especially in the low-income countries where it is highly prevalent. There has been no recent study in Uganda about the factors associated with anaemia in pregnancy. We aimed to assess the current haemoglobin (Hb) status and factors associated with anaemia (Hb < 11.0 g/dl) in pregnant women in Mpigi, Uganda.MethodsWe assessed Hb levels of 2436 pregnant women at 28+ weeks of gestation at six health facilities, who were approached to participate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
58
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 26 publications
18
58
3
3
Order By: Relevance
“…This finding corroborates with previous studies such as in Ethiopia [17] [28], Uganda [29], Nigeria [30], Vietnam [31] and India [32] which indicated that lack of iron supplementation is among the most significant risk factors for developing anaemia during pregnancy. The reason for this might be pregnant women who take their iron tablets which can help them to increase their hemoglobin level and prevent anaemia during pregnancy time.…”
Section: Discussionsupporting
confidence: 93%
“…This finding corroborates with previous studies such as in Ethiopia [17] [28], Uganda [29], Nigeria [30], Vietnam [31] and India [32] which indicated that lack of iron supplementation is among the most significant risk factors for developing anaemia during pregnancy. The reason for this might be pregnant women who take their iron tablets which can help them to increase their hemoglobin level and prevent anaemia during pregnancy time.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with study showed that hemoglobin status of women who had been on iron supplements had a higher mean hemoglobin or women who were not taking iron supplements had approximately 60% higher odds of anemia (p=0.001). 24 This finding is consistent with study done in India showed that those women who had just started to consume, not consuming were 33.3 percent of anemia than those pregnant women were consume full course.…”
supporting
confidence: 89%
“…This observation may be attributed to reduced sample size for those above 40 years and the believe that anaemia in pregnancy increases with rising parity which leads to repeated drain on iron stores [22]. The high prevalence of anaemia among the pregnant women less than 19 years in this study, agrees with the observation of previous authors [11,16] but disagrees with the other researcher [9]. However, the high prevalence amongst the teenage mothers may be associated with lack of awareness or poor knowledge of antenatal services and probably failure to book early at the ANC.…”
Section: Discussionsupporting
confidence: 90%
“…The differences in the prevalence rates of anaemia in pregnant women with age groups of less than 19 years, 20-24 years, 25-29 years, 30-34 years, 35-39 years, and >40 years, were not statistically significant in this research and these results are similar to the findings of other authors [15,16]. However, prevalence of anaemia decreases with increasing age but pregnant women above 40 years had the highest prevalence in this study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation